Exploring Legal Dimensions: The Role of Generation Z and Millennials in Online Lending through the Lens of Islamic Law - Uyun, Linatul; Luthfia, Chaula (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Peer to peer lending or known as Information Technology-Based Money Lending and Borrowing Services is an electronic system financial service that is connected to the internet. Online loans are in great demand because of the ease of transactions, this is what encourages many generation Z and millennial generations as active users of online loans. The sensation of the Fear of Missing Out (FOMO) phenomenon is one that causes social media sites to guide the Millennial lifestyle. Crimes arising from the rise of online loans include the illegal dissemination of data by online loan service providers who deliberately disseminate without consent. The rise of illegal fintech that causes financial losses to individuals and the public who use it. The purpose of this researcher is to see this online loan phenomenon from the perspective of Islamic Law, the universal and dynamic nature that exists in Islamic law answers all problems in human life and the impact caused by online loans. The type of research method used is library research, with a juridical normative approach, which is an approach based on legal norms and the concept of syarî'ah and the rules contained in fiqh and ushul fiqh. The result of this study is that debt receivables through legal technology intermediaries are permissible in Islam. As long as it meets the requirements of the pillars of debt receivables or Qiradh and holds the principles of tawhid and adl. Online loans are not in accordance with Islamic law when Muqridh violates many Qiradh principles such as unclear qirodh shighot, lack of transparency and additional or fines that are not explained in the contract. For Gen Z and Millennials to avoid a consumptive lifestyle, it is necessary to strengthen faith, have gratitude, Qana'ah or an attitude of acceptance and enough.